Idiomatic Phrases among Banten Sundanese Local Language Speakers: An Exploratory Case Study - Dase Erwin Juansah; Akhmad Baihaqi; Aisyah Hamidiyah (Fakultas Adab dan Humaniora, UIN Syarif Hidayatullah Jakarta, Indonesia, 2023)
PurposeThere have been many studies on local languages in Indonesia. However, the study that focuses on Banten Sundanese Language, henceforth is BSL, seems to have not been widely studied, especially its idiomatic phrases. To reach the gaps, this present study aims to explore in-depth investigations about (1) the form of idiomatic phrases in BSL; (2) the use of idiomatic phrases among BSL speakers; and (3) the efforts to preserve the idiomatic phrases in BSL.MethodTo solve the problems, Pandeglang Regency in Banten Province was selected as the locus, and it involved 27 informants who were justified and snowballed. The method used in this research was a case study, with observation, interviews, and documentation as data collecting techniques.Results/findingsThe findings show there are 94 idiomatic phrases in BSL, and most of the informants (63%) claim that the phrases are limited in use.ConclusionIt concludes that real works are emerged in collecting and preserving the BSL phrases through: (a) using BSL as a colloquial language; (b) applying BSL as a compulsory course at both primary and secondary schools; (3) encouraging the regulations to rule the use of BSL among the speakers; (4) publishing BSL dictionary and other literatures; and (5) controlling the use of gadgets, smartphones, and other technological media for the children.